DESIGN AND DEVELOPMENT APPLICATION REGISTRATION AND SELECTION PLACEMENT LEVEL NEW STUDENT WEB-BASED AT RASYID ENGLISH COURSE DENPASAR - Arif, Dimas Lukmannul; Sunarto, M. J. Dewiyani; Mastan, Ignatius Adrian (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
Rasyid English Course is an English language institutions located in strategic locations Monang-Maning area in Denpasar. Rasyid English Course has students as much as seventy to one hundred new students every period of learning. The registration process is still done by filling in the data of prospective new students on enrollment form. This leads to the storage of data in the book as a record of registration documents often have errors and lost of data prospective new students. In addition, the selection process also has a problem in determining the levels for prospective new students. Then Rasyid English Course are expecting their main website as information media that can handle the registration and selection of new student placement level. The testing results show that the registration application and determination selection the level may help the Rasyid English Course and prospective new students. Applications can support the initial registration process by prospective new students who will eventually show suggestions levels to Rasyid English Course. Finally, the registration application and selection can help determine the level of Rasyid English Course in expanding enrollment information and provide convenience to prospective new students through the website.